BACTERIOCINS OF ENTEROTOXIGENIC STAPHYLOCOCCI: CURRENT VIEW OF THEIR ECOLOGICAL AND PATHOGENETIC SIGNIFICANCE IN PEDIATRICS - Коваль, Галина; Мотильчак, Евеліна; Петросова, Валентина (SWorldJournal, 2025)
The aim of the review is to summarize current knowledge on bacteriocins of enterotoxigenic staphylococci, their ecological role in the human microbiota, and their pathogenetic significance in the development of infections in children. The review analyzes